Evaluating groundwater quality through contaminant analysis and water quality index: a case study of Sargodha, Punjab, Pakistan - Khafaga, Doaa Sami; Iqbal, Asifa; Mahmood, Shahid; Shahzad, Arfan; Eid, Marwa M.; Alhussan, Amal Ali; El-Kenawy, El-Sayed M. (Frontiers in Environmental Science, 2025)
Groundwater contamination is a growing concern in water-stressed regions like Sargodha, Punjab, Pakistan. This study aims to assess the physicochemical quality of groundwater using a Water Quality Index (WQI) approach and determine the suitability of groundwater for drinking and irrigation purposes. The samples were collected from a hand pump for 2–3 min to obtain physical results. Thirty groundwater samples were collected from various locations in Sargodha and analyzed for parameters such as pH, total dissolved solids (TDS), sodium (Na), potassium (K), chloride (Cl), calcium (Ca), magnesium (Mg), sulfate (SO4), bicarbonate (HCO3), and nitrate (NO3). The data were obtained through field sampling and tested at the Pakistan Council of Research in Water Resources (PCRWR). The results revealed that TDS, Na, K, and NO3 concentrations in many samples exceeded the permissible limits set by the World Health Organization (WHO). The computed WQI score averaged 84.57, classifying the groundwater as “poor” and generally unsuitable for drinking without treatment, though still usable for irrigation. Results indicate that groundwater pollution contributes to major health challenges, including gastrointestinal, neurological, and chronic diseases. These results highlight the importance of targeted water quality surveillance and public education to prevent potential public health and environmental hazards in the area. These findings provide valuable assistance to policymakers, and environmental agencies to develop more effective interventions to safeguard drinking water for the population in the region.